(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The major objective of this paper was to analyze the effects of factors responsible for the exported quantity of Sudanese live sheep to the market of the Kingdom of Saudi Arabia (KSA). For this end, data on exported quantities, import prices, competitors’ prices, exchange rate and Saudi chilled mutton imports was used. Multiple regression analysis was used for estimating the effect of these factors via a transformed generalized Cobb-Douglas function. Among the four hypothesized variables, only import price and exchange rate were having significant effect on exported live sheep quantities. Consistent with the economic logic, the former was having an elastic effect while the latter had an inelastic effect. The other two variables with insignificant effect were competitors’ price and KSA imported chilled mutton. All four variables exerted increasing returns to scale to the Sudanese exported live sheep quantity. To increase live sheep exports to the Saudi market, the paper recommends improvement of quality control measures, reduction of production cost as well as minimizing the tax margins levied by the different local governments involved, adopting long term contracts in future markets and have Sudan Central Bank adopt exchange rate policy measures to encourage investments in this foreign trade business.